Character Education Based On Local Wisdom To Deal With The Latest Strategic Issues In The Era Of Digitalization Among Youth - Khodijah, Siti; Surawan, Surawan (Proceeding International Conference on Religion, Science and Education, 2025)
An approach to character education based on local wisdom offers a significant and comprehensive solution to the problems currently being faced. In this context, character education plays an important role in forming quality individuals, especially among teenagers who are faced with various complex challenges in the digital era. This research explores the importance of local values in character education as a strategy to strengthen cultural identity, increase creativity, social and moral. As well as facing complex social challenges in the current era of digitalization. Using in-depth interview methods and document analysis, this research concludes that character education that prioritizes local wisdom requires strong support from various parties involved, including teachers, parents, schools and the local community. Collaboration between educational institutions and local communities is considered very important to ensure that local principles remain relevant to today's social and economic demands. From this research it is known that character education based on local wisdom can be an effective tool in preparing the younger generation to face the challenges of the digitalization era well.